2011
DOI: 10.1108/09596111111143340
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of hotel experience of people with disabilities: an exploratory study

Abstract: Purpose-This exploratory study aims to focus on the challenges arising from the interactions between wheelchair users, individuals using crutches and blind people with the hotel environment as well as on the efforts to overcome these challenges. Design/methodology/approach-The sample was gathered through a snowballing technique. The study utilizes in-depth semi-structured interviews of 45 participants: 20 used wheelchairs; ten were dependent on crutches; and 15 were blind. The data were subject to thematic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 45 publications
8
79
0
1
Order By: Relevance
“…Participants of the study (guests, management, and employees) shared the view that the physical attributes of employees with disabilities do not affect their performance or negatively influence the guest experience (Gröschl, 2013). With regard to consumers' perspectives, several hospitality and tourism research focused on the challenges and types of service failures confronted by customers with disabilities (Poria et al, 2011;Kim and Lehto, 2012). A national survey in the USA found that 92 percent of consumers feel more favorable toward companies that hire individuals IJCHM 26,2 with disabilities, and 87 percent agree that they would prefer to give their business to organizations that employ people with disabilities (Siperstein et al, 2006).…”
Section: Service Staff With Disabilitiesmentioning
confidence: 99%
“…Participants of the study (guests, management, and employees) shared the view that the physical attributes of employees with disabilities do not affect their performance or negatively influence the guest experience (Gröschl, 2013). With regard to consumers' perspectives, several hospitality and tourism research focused on the challenges and types of service failures confronted by customers with disabilities (Poria et al, 2011;Kim and Lehto, 2012). A national survey in the USA found that 92 percent of consumers feel more favorable toward companies that hire individuals IJCHM 26,2 with disabilities, and 87 percent agree that they would prefer to give their business to organizations that employ people with disabilities (Siperstein et al, 2006).…”
Section: Service Staff With Disabilitiesmentioning
confidence: 99%
“…A. Lee & Jeong, 2014), experiential value (Wu & Liang, 2009), pricing of experience products (Adhikari, Basu, & Raj, 2013), experience economy (Loureiro, 2014;Scott, Laws, & Boksberger, 2009), quality of experience (Xu & Chan, 2010), hotel experience of people with disabilities (Poria, Reichel, & Brandt, 2011), and dining experience (Lord, Putrevu, & Parsa, 2004;Wijaya, King, Nguyen, & Morrison, 2013), HBE has received little research attention.…”
Section: Brand Experience Research In Hotel Industry: a Theoretical Bmentioning
confidence: 99%
“…Öncelikle engellilerin sosyal hakları olan çevre, fiziksel donanım ve çalışan davranışları ile ilgili rahatsızlıkları bulunmaktadır. Turizm sektöründe faaliyet gösteren işletmeler tarafından bu konuda engellilerin karşılaştığı zorlukların ortadan kaldırılmasına yönelik uygulamaların gerçekleştirilmesi de oldukça önemlidir (Poria, Reichel & Brandt, 2011).…”
Section: Introductionunclassified